At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

If [tex]$f(x)=3x^2+1$[/tex] and [tex]$g(x)=1-x$[/tex], what is the value of [tex][tex]$(f-g)(2)$[/tex][/tex]?

A. 12
B. 14
C. 36
D. 38


Sagot :

To determine the value of [tex]\((f - g)(2)\)[/tex], we first need to find the individual values of [tex]\(f(2)\)[/tex] and [tex]\(g(2)\)[/tex].

### Step 1: Calculate [tex]\(f(2)\)[/tex]
The function [tex]\(f(x)\)[/tex] is defined as:
[tex]\[ f(x) = 3x^2 + 1 \][/tex]

Plugging in [tex]\(x = 2\)[/tex]:
[tex]\[ f(2) = 3(2)^2 + 1 \][/tex]
[tex]\[ f(2) = 3 \times 4 + 1 \][/tex]
[tex]\[ f(2) = 12 + 1 \][/tex]
[tex]\[ f(2) = 13 \][/tex]

### Step 2: Calculate [tex]\(g(2)\)[/tex]
The function [tex]\(g(x)\)[/tex] is defined as:
[tex]\[ g(x) = 1 - x \][/tex]

Plugging in [tex]\(x = 2\)[/tex]:
[tex]\[ g(2) = 1 - 2 \][/tex]
[tex]\[ g(2) = -1 \][/tex]

### Step 3: Calculate [tex]\((f - g)(2)\)[/tex]
The expression [tex]\((f - g)(x)\)[/tex] represents the difference between the functions [tex]\(f\)[/tex] and [tex]\(g\)[/tex] at [tex]\(x\)[/tex], which is given by:
[tex]\[ (f - g)(x) = f(x) - g(x) \][/tex]

So, we need to find [tex]\((f - g)(2)\)[/tex]:
[tex]\[ (f - g)(2) = f(2) - g(2) \][/tex]

Substituting the values we previously found:
[tex]\[ (f - g)(2) = 13 - (-1) \][/tex]
[tex]\[ (f - g)(2) = 13 + 1 \][/tex]
[tex]\[ (f - g)(2) = 14 \][/tex]

Thus, the value of [tex]\((f - g)(2)\)[/tex] is [tex]\(\boxed{14}\)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.